Association of Nutritional, Functional Status and Lifestyle Habits with Bone Health Status Amongst the Institutionalized Elderly - Tee, Chin Kim (2007)
The rising incidence of osteoporosis is well established especially among institutionalized residents. The aim of the study was to determine the association of nutritional status, functional status and lifestyle habits with bone health status among institutionalized elderly. Bone health status was assessed using Quantitative Ultrasound Sonometry (QUS-2), which measures Broadband Ultrasound Attenuation (BUA, dB/MHz) at the calcaneus. Body weight, height and body fat were assessed using SECA 767 and body fat analyzer (HBF-302 Omron). Sociodemographic background, reproductive history, history of bone fracture, lifestyle habits, dietary intake and functional status (Elderly Mobility Scale-EMS and Instrumental Activity Daily Living- IADL) of the subjects were assessed using appropriate instruments. Data were analyzed using SPSS software version 13.0 and Malaysian food composition database A total of 363 subjects comprising of 158 males (43.5%) and 205 females (56.5%) were recruited from 33 old folk’s homes and nursing homes in the Klang Valley. The subjects comprised of 79.3% Chinese, 11.6% Indians, 5.5% Malays and other races (3.6%). The mean age of the subjects was 75.8 ± 9.1 years old. The mean weight, height and body fat mass for male and female were 56.7 ± 11.9 and 50.6 ± 13.8, 161.9 ± 7.7 and 149.5 ± 11.7, 15.6 ± 7.0 and 16.7 ± 11.8, respectively. Mean Body Mass Index (BMI) for male and female were 21.6 ± 4.3kg/m 2 and 22.4 ± 5.6 kg/m 2 . Based on BMI classification, 23.3% of the subjects were underweight, 52.9% with normal weight and 23.8% were overweight and obese. The mean BUA was 61.4 ± 19.8 dB/MHz. Majority of the subjects had second tertile of BUA and there was only 10.0% of subject with third tertile of BUA. The mean energy intake was 1311 ± 312 Kcal. The mean calcium intake was low, with 428 ± 277 mg in males and 454 ± 281 mg in females. More than 50% of the subjects had daily calcium intake less than RNI for Malaysian. Approximately half of the subjects achieved 75 th percentile for EMS. However, score for IADL was low, with a mean of 8.6 ± 4.6. There were 61.7% of subjects who exercised currently with a majority of them practicing brisk walking. The results revealed significant correlation between BUA and weight (r=0.390, p<0.01), fat mass (r=0.156, p<0.01), phosphorus intake (r=-0.148, p<0.05), protein intake (r=-0.121, p<0.05), vitamin C (0.120, p<0.05), EMS (r=0.241, p<0.01) and IADL (r=0.250, p<0.01), duration exercise per session (r=0.138, p<0.05). Body weight, IADL score, and vitamin C intake were the main contributors for bone health status among the subjects, which explain 21.5% of the variation in the BUA significantly (p<0.001). As a conclusion, institutionalized elderly should be given better care or intervention in achieving optimal body weight and dietary intakes through providence of better nutrition and rehabilitation efforts to improve functional status.